2010
DOI: 10.14214/sf.125
|View full text |Cite
|
Sign up to set email alerts
|

Productivity of the M-Planter tree-planting device in practice

Abstract: Need to mechanise tree-planting work have recently increased for many reasons. The newest planting and soil scarification device performing work in Nordic forests is the Finnish M-Planter. This study aims to clarify M-Planter's productivity in practice and show how various factors affect it. The follow-up data set covers 607 work shifts, of 13 operators with, in total, five M-Planters. The average productivity figures for the operators were 143 and 169 seedlings per effective working hour during the first and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 6 publications
1
30
1
Order By: Relevance
“…Also, Finnish contractors more often had two client companies and operated in two shifts per day, while Swedish contractors typically only had one client company and operated in a single shift per day. Still, annual use [29,30] (or more specifically Capacity Utilization [31] or Total Utilization [12]) of the Swedish planting machines was typically almost the same as the Finnish machines (in terms of average number of shifts per year: 150 vs. 160; Table 1) because of southern Sweden's longer planting season (typically 7 months vs. 5 months; Table 1). …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Also, Finnish contractors more often had two client companies and operated in two shifts per day, while Swedish contractors typically only had one client company and operated in a single shift per day. Still, annual use [29,30] (or more specifically Capacity Utilization [31] or Total Utilization [12]) of the Swedish planting machines was typically almost the same as the Finnish machines (in terms of average number of shifts per year: 150 vs. 160; Table 1) because of southern Sweden's longer planting season (typically 7 months vs. 5 months; Table 1). …”
Section: Discussionmentioning
confidence: 99%
“…This is contrary to our key factor "Contractors having several client forest companies", but the harvesting contractors in Mäkinen's study worked year around and were reported to have Capacity Utilization rates up to 99%. Planting machines, in Finland especially, cannot work year around, and tend to have one-third as high Capacity Utilization rates [12]. Thus, during the short Fennoscandian planting seasons, efficient route planning and small operating radii (the latter which multiple clients can give rise to) become comparatively more important for planting machines if they are to secure enough productive hours to pay for their capital costs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations